Development of a national occupational safety and health programme in Ukraine: gender aspekt - Lagutina, I.; Лагутина, Ирина Викторовна; Лагутіна, Ірина Вікторівна (My University, 2012)
The article emphasizes that decent work is recognized as the ﬁ rst step towards greater social integration and to create conditions for comprehensive development of the individual, realization of personal non-property labour rights. Of particular importance is the provision of safe work as components of the concept of "decent work".
Lagutina I. Development of a national occupational safety and health programme in Ukraine: gender aspekt / I. Lagutina // Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред.), Л. І. Кормич (заст. голов. ред.), Ю. П. Аленін [та ін.] ; МОНмолодьспорт України, НУ ОЮА. - Одеса : Фенікс, 2012. – Вип. 45. – С. 196-203.
Keywords: соціальна інтеграція; всебічний розвиток особистості; реалізація особистих немайнових трудових прав; забезпечення безпечної праці; социальная интеграция; всестороннее развитие личности; реализация личных неимущественных трудовых прав; обеспечение безопасного труда; social integration; all-round development of the personality; realization of moral labor rights; occupational safety